SISTEM INFORMASI INVENTORY P.O.S (POINT OF SALES) BERBASIS WEB PADA COUNTER CELLULAR - Yuggo Afrianto; Novita Br Ginting; Suratun Suratun; Yashintya Nelawati (STMIK Royal, 2020)
Abstract: Data from the National Socio-Economic Survey of the National Central Bureau of Statistic (Susenas, BPS) 2016 shows that the average amount of national top up the balance spending per month in 2016 reaches Rp 22,182 per capita. It is becoming a business opportunity for top up the balance of retail entrepreneurs. However, in the process of managing the process of input, output and reporting of goods that are done manually (still using paper) are not monitored properly, often there are outgoing or incoming goods whose data is not recorded. This, in the long run, will cause large losses. The purpose of this study is to build applications that function to help provide information that makes it easy to control the process of entry and exit of goods. The system development methodology used is object-oriented system development using the Unified Modeling Language (UML). The results obtained from this research are the design and construction of Inventory Information System POS (Point of Sales) in the form of Context Diagrams and UML Diagrams (Use Case Diagrams, Activity Diagrams, Class Diagrams, and Sequence Diagrams), with the results of black box testing conducted already in operation properly according to the needs of the retail owner. Keywords: Point of Sales, Retail, UML Abstrak: Data Survei Sosial Ekonomi Nasional Badan Pusat Statistik (Susenas, BPS) 2016 menunjukkan, jumlah rata-rata pengeluaran pulsa secara nasional per bulan pada 2016 mencapai Rp 22.182 per kapita [1]. Tentu saja hal ini menjadi peluang usaha untuk para pengusaha retail counter. Namun, dalam proses pengelolaannya proses input, output dan pelaporan barang yang dilakukan secara manual (masih menggunakan kertas) tidak termonitoring dengan baik, seringkali terjadi adanya barang keluar ataupun barang masuk yang tidak tercatat datanya. Hal ini dalam jangka panjang akan menimbulkan kerugian yang besar. Tujuan penelitian ini adalah membangun aplikasi yang berfungsi dalam membantu memberikan informasi yang memudahkan dalam pengontrolan proses keluar masuknya barang. Metodologi pengembangan sistem yang digunakan adalah pengembangan sistem berorientasi objek menggunakan Unified Modeling Language (UML). Hasil yang didapat dari penelitian ini adalah perancangan dan pembangunan Sistem Informasi Inventory P.O.S (Point of Sales) berupa Diagram Konteks dan UML Diagram (Use Case Diagram, Activity Diagram, Class Diagram, dan Sequence Diagram), dengan hasil pengujian black box yang dilakukan telah beroperasi dengan baik sesuai kebutuhan owner retail. Kata kunci: Point of Sales, Retail, UML